We have never been woke the cultural contradictions of a new elite - al-Gharbi, Musa 1983-; Princeton University Press (Princeton Oxford Princeton University Press, 2024)
"A book that explores the disconnect between the ideals of the Great Awokening and the realities of fixing structural inequality. This book aims to explain how a new elite has risen to prominence and established a social order that is fundamentally premised on exclusion, exploitation and condescension even as its members define themselves in terms of their commitments to uplifting the marginalized and disadvantaged. The book will illustrate how this core tension within the new elite explains a number of trends we've seen, from the Great Awokening to growing political polarization and beyond. We Have Never Been Woke will draw from and build upon al-Gharbi's work over the last six years that has examined the rise of Trump, the crisis of expertise, tensions over 'identity politics' and growing social inequality. It will demonstrate each of these domains as a 'front' of a broader social and cultural conflict - a conflict between those who have come to dominate the 'knowledge economy' and institutions of cultural production and those who feel excluded therefrom. It will highlight the ways symbolic analysts - those elites who have not attained their social position by owning material assets but by trafficing in symbols and rhetoric, images and narratives, data and analysis - deploy wokeness as a weapon in this conflict, often at the expense of those who are actually marginalized and disadvantaged in the prevailing order. As We Have Never Been Woke will demonstrate, the Americans who are the primary producers and consumers of content on antiracism, socialism, feminism, etc. also happen to be the primary beneficiaries of gendered, racialized and other forms of inequality - and not passive beneficiaries. We are active participants in exploiting and reproducing inequalities. However, it is difficult for us to 'see' how we contribute to the problem -- precisely because of our deeply felt commitments to social justice. This book aims to deflate these self-serving narratives while dismantling popular (and self-serving) narratives about the 'losers' in the system - leaving readers with a totally different understanding of how social inequality is produced (and by whom), and unnerving questions about what it would take to meaningfully address it".
References: p. 363 - 418
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Social Conflict -- United States -- History -- 21st century; Social Justice -- United States -- History -- 21st century; Equality -- United States -- History -- 21st century; Identity Politics -- United States -- History -- 21st century; Power (Social sciences) -- United States -- History -- 21st century; Wokeismus